2022
DOI: 10.1038/s41598-022-19789-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical characteristics of cervical spine injuries in older adults by external causes: a multicenter study of 1512 cases

Abstract: Although traumatic cervical spine injuries in older adults are commonly caused by minor traumas, such as ground-level falls, their prognosis is often unfavorable. Studies examining the clinical characteristics of cervical spine injuries in older adults according to the external cause of injury are lacking. This study included 1512 patients of ≥ 65 years of age with traumatic cervical spine injuries registered in a Japanese nationwide multicenter database. The relationship between the external causes and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Our data showed that 304 (20%) of the 1512 patients 65 years or older with SCI had no major bone injury and that SCI in 20% of the patients was caused by low-energy trauma. 16 , 17 Therefore, we think that the occurrence rate of 3.5% in the elderly patients was lower than that typically seen in young and adult patients. Previous articles have not reported the risk factors based on AO classifications.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Our data showed that 304 (20%) of the 1512 patients 65 years or older with SCI had no major bone injury and that SCI in 20% of the patients was caused by low-energy trauma. 16 , 17 Therefore, we think that the occurrence rate of 3.5% in the elderly patients was lower than that typically seen in young and adult patients. Previous articles have not reported the risk factors based on AO classifications.…”
Section: Discussionmentioning
confidence: 78%
“…In total, 1512 patients from 33 nationwide institutions were enrolled in this study (average age: 75.8 ± 6.9 years; 1007 males, 505 females). 16 , 17 Data including age at injury, sex, height and weight at first visit, past/present cigarette smoking, spinal surgery for the CSI, and comorbidities (hypertension, cerebrovascular disease, cardiovascular disease, ossification of posterior longitudinal ligament [OPLL] and head injury) were collected. Characteristics of the study population are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients whose treatment course and outcome were unclear were excluded. Data collection was performed using the multicenter database of the Japan Association of Spine Surgeons with Ambition [ 21 ]. Traumatic cervical spine injuries included (1) isolated cervical fractures and/or dislocations, (2) isolated spinal cord injury, and (3) spinal cord injury with fractures and/or dislocations.…”
Section: Methodsmentioning
confidence: 99%